Investigation of the Spontaneous Spin-Flip Phase Transition in Terbium-yttrium Iron-Garnet by the Magnetooptic Method - Djuraev, D.R.; Niyazov, L.N.; Saidov, K.S.; Sokolov, B.Yu. (Ukrainian Journal of Physics, 2012)
The domain structure transformation and the technical magnetization of a Tb0.26Y2.74Fe5O12 single crystal have been studied by the magnetooptic method in the temperature region of a spontaneous spin-flip phase transition (SFPT). It has been found that the SFPT occurs in a finite temperature interval, where the low- and high-temperature magnetic phase domains coexist. We have observed the anomalies of the temperature dependences of the coercive force and the magnetooptic susceptibility of the crystal related to a transformation of its domain structure under the spin-flip. The experimental results obtained are interpreted within the framework of the SFPT theory for a cubic crystal. It has been demonstrated that the existing theory describes consistently the evolution of the Tb0.26Y2.74Fe5O12 garnet domain structure under the spontaneous reorientation of the easy magnetization axis.